Patriotism, black politics and racial justice in America. Issue 3 (2nd July 2016) - Burkey, Maxwell; Zamalin, Alex
Abstract: Recent decades have seen an upsurge in interest in patriotism among progressive intellectuals and within progressive politics, while recent manifestations of black politics in the era of President Barack Obama have utilized patriotic narratives. We question this turn to patriotism on the grounds that it is a questionable manner in which to pursue racial justice in our post-Civil Rights political landscape. Patriotic appeals to civic virtue always invoke or imply the anti-patriot who lacks that virtue and is therefore less capable of exercising exemplary citizenship. This idea of the anti-patriot, however, easily coalesces with and buttresses the language of cultural pathology used historically to argue that African-Americans are deficient in civic virtue and key for reproducing racial inequality. The idea of the anti-patriot could thus provide another vocabulary for displacing responsibility for addressing racial inequality away from white Americans and onto black Americans. After illuminating this dynamic at work in some of the most successful African-American patriotic thinkers—Frederick Douglass, Martin Luther King, Jr., and Barack Obama—we conclude by arguing that those concerned with racial justice should reject patriotism in favor of three alternative traditions in African-American political thought: self-examination, prophecy, and rage.